Legal Protection of Compost Fertilizer Technology Patent in Celincing Mangrove Forest Tourism - Selvianti, Isye; Marisa Nopriyanti (Universitas Muhammadiyah Surabaya, 2025)
This study aims to determine and analyze the legal protection efforts of compost fertilizer inventors from mangrove waste in Suka Baru village, Ketapang Regency, West Kalimantan and to determine and analyze the patent registration system for compost fertilizer products from mangrove waste in Suka Baru village. The method used in this research is normative-empirical research using primary data, namely the results of interviews and secondary data containing primary and secondary legal materials. The results of the research show that compost fertilizer from mangrove waste in Suka Baru village has not received legal protection due to the lack of public understanding of the importance of Patentability, and the Patent registration system applied by Indonesia, namely the first to file system which recognizes the owner of the Patent Rights (Invention) who registers first. Therefore, if this problem is not followed up immediately, it will trigger various problems that will be caused such as claims from other parties and so on.